The Light and the Darkness : Studies in Manichaeism and its World - Mirecki, Paul,; BeDuhn, Jason, (Nag Hammadi and Manichaean Studies ;, 2001)
This is the second volume of scholarly studies in Manichaeism which were originally presented before the Manichaean Studies Group of the Society of Biblical Literature from 1997 through 1999. Like its predecessor, Emerging from Darkness: Studies in the Recovery of Manichaean Sources (Brill, 1997), this volume presents the latest international scholarship from leading researchers in the growing field of Manichaean studies. Here the researchers move from the continuing foundational work of recovering Manichaean sources to the necessary task of understanding the relationship of Manichaeans to the larger world in which they lived. That relationship took several distinct forms, and the contributions in this book analyze those forms, examining the relationship of Manichaeism with diverse cultural, social and religious traditions.